Tackle-based head injury assessment (HIA) risk factors in the National Rugby League: Does the ball carrier`s evasion technique or the tackler`s head position influence HIA risk? - Carlton-Greaves, S.; Edwards, S.; Jones, B.; Tucker, R.; Iverson, G. L.; Gardner, A. J. (European Journal of Sport Science, 2026)
Rugby-style tackle techniques have been evaluated for a number of years and have traditionally focused on injury prevention and performance outcomes. Recent tackle technique research has increasingly been directed towards reduced head contact and reducing the risk for concussion. This video analysis study examined the association between the ball carrier's evasion technique and the tackler's head position and the risk for a Head Injury Assessment (HIA) in professional male rugby league players. Retrospective video analysis cohort study. Three seasons of National Rugby League (NRL) head injury assessment (HIA) events (n = 446) were retrospectively video coded. For comparison and the calculation of propensity, 5694 tackles that did not result in a head injury were also coded. In this study, the two variables of interest were the ball carrier's evasion technique and the tackler's head position. Propensity was calculated as HIAs per 1000 tackles. The results of this study demonstrate the highest proportion of HIAs occurred when ball carriers did not utilise an evasion strategy and when the tacklers positioned their head in front of the ball carrier, especially when combined with high-risk evasion strategies such as jumping or shoulder charging. HIA prevention initiatives should consider tackle techniques that encourage tacklers to place their head beside the ball carrier and ball carrying strategies that utilise an evasion technique, such as twisting or bending the torso. Further tackle-based research is required in female and youth players to evaluate whether the findings in elite male players generalise to other rugby league players.